Fecal Sludge Recycling to Useful Products: Environmental Concerns, Viability and Potential (Applied Research and Innovation, 2023)
Biofertilizer, biogas and the chemical substances in those two, which are generated as a result of several treatment methods fecal sludge (FS) are usually subjected to, can be recovered for diverse applications. The treatment methods are classified into traditional and innovative methods. FS sludge impacts the environment negatively and one of the most adopted methods for its treatment from toilets where they originate, are composting and anaerobic digestion to recover biogas and organic fertilizer. FS potential for biogas production has been critically examined here using literature sources. It is discovered that FS is not largely favored as a means of recovering bioenergy in most parts of the world due to hygiene concerns, even though it is one of the most abundant organic materials for bioenergy recovery through anaerobic digestion. This work hence studied the factors hindering FS recycling and reuse, which it convincingly addresses. The work also demonstrates ways FS can be safely collected and digested to useful products and make a case for future investment in the sector by relevant bodies due to its feasibility, profitability and environmental-friendliness. Implementation of a system that recovers FS from latrines of households and public places and converts them to useful products are therefore recommended.